Extraction and antioxidative activity of essential oil from star anise (Illicium verum) - Lee, Poh Peng (2014)
Long term and extensive use of synthetic antioxidant such as butylated hydroxytoluene (BHT) in cosmetic formulation has been proven to cause carcinogenic effects in living organisms. Due to the potential side effects of synthetic antioxidants, essential oil which derived from organic products can be served as an alternative source for the further improvement of synthetic antioxidant. Star anise (Illicium verum) is a potential alternative antioxidant source due to its presence of high level of active compound known as anethole. The objectives of this study are to extract essential oil from star anise using solvent extraction method. to determine the yields and antioxidant activities of essential oils at different extraction times and temperatures and to validate the presence of trans-Anethole using HPLC analysis. The optimum condition to obtain higher yield of essential oil was at 60 °C with an extraction time of 7 days. The antioxidant activities of the extracted star anise essential oils were investigated using 2, 2-dipheny1-1-picrylhydrazyl (DPPH) assay on TLC plates and DPPH radical scavenging method. Highest antioxidant activity of star anise essential oil was obtained when the sample was extracted at 60 °C for 1 day (antioxidant activity=77.76±0.15 % with EC50 value of 0.089±0.05 mg/ml). The HPLC analysis showed that concentration (%) of trans-Anethole was corresponded to the antioxidant activities of the star anise essential oils. Star anise essential oils. particularly those extracted at 50°C and 60°C showed a marked antioxidant activity potential, hence they could be developed and used as a natural source of antioxidant in cosmetic productions.